A Novel Mechanism for Enhancement and Detection of Retinal Blood vessels - Manjot Kaur, Dr. Amit Kamra (International Journal of Advanced Science and Technology, 2018)
Diabetic retinopathy (DR) has been recognized as a major cause of blindness among working-age adults. It’s a chronic eye disease that can reach to irreversible vision loss. Its early detection is important for a good prognosis. Of those who have diabetes, around one-third suffers from diabetic retinopathy. This research paper focuses on enhancing the diabetic retinal images to get augmented retinal images which may assist in the early detection of the disease. The enhancement has been achieved by applying multiple filter techniques systematically along with modified mathematical calculations. The detailed working of the adopted methods is deeply explained in the research paper with algorithms and appropriate mathematical equations wherever required. The readings of PSNR, MSE, and RMSE revealed in the tables mentioned in the results and discussion section approves the worth of the research work conducted in enhancing retinal images. The proposed technique proved to more effective when compared with existing methodsKeywords: Enhancement, Fundoscopic Images, Power-law, Retina